Foreign Direct Investment and Women Empowerment : New Evidence on Developing Countries - Ouedraogo, Rasmane (IMF Working Papers; Working Paper, 2018)
This paper assesses the effects of foreign direct investment (FDI) on gender development and gender inequality. In fact, FDI through increased labor demand, technological spillovers but mostly through corporate social responsibility and economic growth, can potentially influence women's welfare. Using a panel dataset of 94 developing countries from 1990 to 2015, we find that FDI inflows improve women's welfare and decrease gender inequality. However, the impact is lower in countries where women have low access to resources and face a heavier burden to open a business. This suggests that for countries to fully benefit from FDI inflows, they should ensure that women can enjoy free access to the labor market and associated income.